Malarial Landscapes in Late Antique Rome and the Tiber Valley. (2nd July 2016) - Ziegler, Michelle
ABSTRACT: Using malaria and the watershed of the River Tiber as an example, this essay demonstrates how the principles of landscape epidemiology – taking the natural and human landscapes as a whole – can guide investigations into historic landscapes of disease. 'Roman fevers' have been legendary since Antiquity, and Italy's malarial landscape was one of the most well known in the world. As this essay will illustrate, the Late Antique Tiber Valley was primed to support an intense malarial landscape continuing from Imperial Rome forward to medieval Italy with a continuing role in an urban syndemic, the convergence of two or more diseases into a larger problem. Studies by Sallares, Aldrete and others have provided the evidence needed to apply the principles of landscape epidemiology to Rome and the Tiber Valley. Taking into account climate, landscape features, animal species and human activity provides a more complete or holistic assessment of how an infectious disease functioned in the region.